Xeroderma Pigmentosum: A Bane in developing country - Brief report - Hari Kishan Kumar Yadalla; Syeda Juwariya (Our Dermatology Online, 2014)
Xeroderma pigmentosum (XP) is a rare autosomal recessive disorder characterized by photosensitivity, cutaneous pigmentary changes, premature skin ageing, and the development of various cutaneous and internal malignancies at an early age. We present this case of a 10 year-old girl in a developing country like India, with significant corneal scarring and multiple cutaneous skin lesions in sun-exposed areas. Developmental delay had been present since 3 months of age, with these clinical features it was consistent with Xeroderma Pigmentosum. We highlight the difficulties encountered due to the lack of diagnostic and treatment modalities for this child, and offer a brief review of XP, including emerging treatments.